Effects of different types of core training on pain and functional status in patients with chronic nonspecific low back pain: a systematic review and meta-analysis - Guo, Xu Bin; Lan, Qiuxi; Ding, Junyi; Tang, Lu; Yang, Mingliang (Frontiers in Physiology, 2025)
BackgroundChronic non-specific low back pain (CNSLBP) represents a leading cause of global disability, with core training emerging as a promising non-pharmacological intervention. However, the comparative effectiveness of different core training modalities remains unclear. This systematic review and meta-analysis aimed to comprehensively compare the differential effects of three core training approaches—Pilates training, core stability training, and core resistance training—on pain intensity, functional status, and quality of life in adults with CNSLBP.MethodsA comprehensive systematic search was conducted across four electronic databases (Web of Science, PubMed, Cochrane Library, and Scopus) from inception to May 2025, following PRISMA guidelines. We included randomized controlled trials comparing Pilates training, core stability training, or core resistance training with control conditions in adults aged 18–65 years with CNSLBP ≥12 weeks. Primary outcomes included pain intensity (assessed using Visual Analog Scale [VAS] or Numerical Rating Scale [NRS]) and functional disability (measured by Oswestry Disability Index [ODI] or Roland-Morris Disability Questionnaire [RMDQ]). Secondary outcomes encompassed quality of life measures (SF-36). Risk of bias was assessed using the Cochrane RoB 2.0 tool. Random-effects meta-analysis was performed, with standardized mean differences (SMD) calculated for effect sizes. Meta-regression analysis was conducted to identify optimal training parameters.ResultsA total of 57 randomized controlled trials involving 7,705 participants were included. All three core training modalities demonstrated significant improvements in pain relief compared to controls (SMD = 0.70; 95% CI: 0.58–0.82; p < 0.00001; I2 = 47%). Subgroup analysis revealed differential effects: Pilates training showed optimal pain relief effects (SMD = 0.75; 95% CI: 0.58–0.92), followed by core resistance training (SMD = 0.68; 95% CI: 0.56–0.80) and core stability training (SMD = 0.53; 95% CI: 0.34–0.73). For functional status improvement, core resistance training demonstrated the most significant and stable effects (SMD = 0.76; 95% CI: 0.55–0.97; I2 = 0%), while Pilates training (SMD = 0.71; 95% CI: 0.13–1.56) and core stability training (SMD = 0.52; 95% CI: 0.33–0.70; I2 = 0%) showed moderate improvements. Although the effect sizes for Pilates, core stability training, and core resistance training showed numerical differences, the statistical comparison did not reach significance (P = 0.24) for improving pain and functional status. Meta-regression analysis identified optimal training parameters: core resistance training 3-4 sessions per week (30–45 min per session), Pilates training 2-3 sessions per week (50 min per session, 8–12 weeks duration), and core stability training 3-4 sessions per week (40–60 min per session, 6–8 weeks duration). Training frequency emerged as the strongest predictor of pain improvement in core resistance training (β = 0.48; p = 0.007). All three modalities showed limited effects on mental health components of quality of life.ConclusionThis study provides the first comprehensive evidence-based comparison of core training modalities for CNSLBP management. Pilates training demonstrates superior effectiveness for pain relief, while core resistance training shows optimal benefits for functional improvement. The identification of specific dose-response relationships and optimal training parameters offers precise clinical guidance for individualized exercise prescription. Core training represents a safe, effective, evidence-based non-pharmacological treatment approach, with clinical application requiring tailored selection based on patient-specific symptoms and treatment objectives. Future research should focus on long-term efficacy evaluation and development of personalized intervention protocols.Systematic Review RegistrationPROSPERO CRD420251054431.